Immunogenic cell death after combined treatment with radiation and ATR inhibitors is dually regulated by apoptotic caspases - Eek Mariampillai, Adrian; Hauge, Sissel; Kongsrud, Karoline; Syljuåsen, Randi G. (Frontiers in Immunology, 2023)
Introduction Inhibitors of the ATR kinase act as radiosensitizers through abrogating the G2 checkpoint and reducing DNA repair. Recent studies suggest that ATR inhibitors can also increase radiation-induced antitumor immunity, but the underlying immunomodulating mechanisms remain poorly understood. Moreover, it is poorly known how such immune effects relate to different death pathways such as caspase-dependent apoptosis. Here we address whether ATR inhibition in combination with irradiation may increase the presentation of hallmark factors of immunogenic cell death (ICD), and to what extent caspase activation regulates this response. Methods Human lung cancer and osteosarcoma cell lines (SW900, H1975, H460, U2OS) were treated with X-rays and ATR inhibitors (VE822; AZD6738) in the absence and presence of a pan-caspase inhibitor. The ICD hallmarks HMGB1 release, ATP secretion and calreticulin surface-presentation were assessed by immunoblotting of growth medium, the CellTiter-Glo assay and an optimized live-cell flow cytometry assay, respectively. To obtain accurate measurement of small differences in the calreticulin signal by flow cytometry, we included normalization to a barcoded control sample. Results Extracellular release of HMGB1 was increased in all the cell lines at 72 hours after the combined treatment with radiation and ATR inhibitors, relative to mock treatment or cells treated with radiation alone. The HMGB1 release correlated largely – but not strictly – with loss of plasma membrane integrity, and was suppressed by addition of the caspase inhibitor. However, one cell line showed HMGB1 release despite caspase inhibition, and in this cell line caspase inhibition induced pMLKL, a marker for necroptosis. ATP secretion occurred already at 48 hours after the co-treatment and did clearly not correlate with loss of plasma membrane integrity. Addition of pan-caspase inhibition further increased the ATP secretion. Surface-presentation of calreticulin was increased at 24-72 hours after irradiation, but not further increased by either ATR or caspase inhibition. Conclusion These results show that ATR inhibition can increase the presentation of two out of three ICD hallmark factors from irradiated human cancer cells. Moreover, caspase activation distinctly affects each of the hallmark factors, and therefore likely plays a dual role in tumor immunogenicity by promoting both immunostimulatory and -suppressive effects.